2009
DOI: 10.5009/gnl.2009.3.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Prognosis of Spontaneous Bacterial Peritonitis in Korean Patients with Liver Cirrhosis: A Multicenter Retrospective Study

Abstract: Background/AimsAlthough early recognition and treatment with effective antibiotics have lead to improvements in the prognosis of patients with spontaneous bacterial peritonitis (SBP), it remains to be a serious complication in cirrhotic patients. This study was designed to evaluate the clinical manifestations and prognosis of patients with liver cirrhosis and SBP in Korea.MethodsThis was a multicenter retrospective study examining 157 episodes of SBP in 145 patients with cirrhosis. SBP was diagnosed based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 41 publications
6
41
3
2
Order By: Relevance
“…[13][14][15][16] Although the mean age among the individuals with SBP was somewhat lower than previously described by other authors (52.8 to 58.4 years), [13][14][15][16] in line with what was found in the present study. 14,16,19 With regard to the etiology of cirrhosis, Heo et al reported…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[13][14][15][16] Although the mean age among the individuals with SBP was somewhat lower than previously described by other authors (52.8 to 58.4 years), [13][14][15][16] in line with what was found in the present study. 14,16,19 With regard to the etiology of cirrhosis, Heo et al reported…”
Section: Discussionsupporting
confidence: 92%
“…Flowchart of potential candidates for inclusion in the study, application of exclusion criteria and individuals included. followed by alcoholic cirrhosis (19.7%) and cirrhosis by HCV (6.4%), 16 and these data are consistent with the high prevalence of HBV in Asia. [20][21][22] In North America, Heidelbaugh et al reported…”
Section: Discussionsupporting
confidence: 77%
“…ESBL-E are predominant in Southern Europe and Asia [7,[13][14][15][16][17][18][19][20][21][22][23][24][25] , meanwhile MRSA and VRE are prevalent in the United States [26] . Carbapenemase-producing K. pneumoniae is a current problem described in some hospitals in Italy [27] .…”
Section: Diversity Of Mr Bacteria Types Across Countriesmentioning
confidence: 99%
“…Regular epidemiology assessment should be carried out in all centers and policies regarding empiric antibiotic treatment in cirrhosis should be updated and tailored according to the specific epidemiological pattern of 918 May 8, 2015|Volume 7|Issue 7| WJH|www.wjgnet.com [13,14,19,20,24] Italy, 8%-20% [17,21] Spain and United States, 6%-9% [7,15,26] France, Denmark and Germany, < 5% [22,23,25] MRSA Italy, 7% [17,21] United States, 5% [26] Spain, 3%-4% [7,15] France, 2% [23] Denmark, Germany, 0% [22,25] Pseudomonas aeruginosa Spain, South Korea, 2%-3% [7,[13][14][15]19,20,24] Germany, 1% [22] Denmark, France, 0% [23,25] VSE Denmark, 12% [25] Germany, 10% [22] France, 5% [23] Spain, 1%-7% [7,15] VRE United States, 9% [26] Spain, France, Denmark, Germany, 0% [7,15,22,23,25] ESBL: Extended-spectrum β-lactamase-producing Enterobacteriaceae (bacteria with chromosomal β-lactamases are also included); MRSA: Methicillinresistant Staphylococcus aureus; VSE: Vancomycin-susceptible Enterococcus; VRE: Vancom...…”
Section: Changing the Empirical Antibiotic Treatment Of Bacterial Infmentioning
confidence: 99%
“…Treatment with albumin is particularly effective in patients with serum bilirubin ≥ 4 mg/dL or serum creatinine ≥ 1 mg/dL, while its use in patients without these criteria remains controversial [49] . However, in unselected patients with SBP, even low-dose albumin (10 g/d on day 1 and 3) reduces tumour necrosis factor and interleukin 6 levels in serum and ascites as well as preventing increases in serum nitric oxide induced by SBP [50] .…”
Section: Treatment Of Community-acquired Sbpmentioning
confidence: 99%